Magnetization plateaus in dimerized spin-ladder arrays - Cabra, Daniel Carlos (2000)
We investigate the ground-state magnetization plateaus appearing in spin-½ two-leg ladders built up from dimerized antiferromagnetic Heisenberg chains and dimerized zig-zag interchain couplings. Using both Abelian bosonization and Lanczos methods we find that the system yields rather unusual plateaus and exhibits massive and massless phases for specific choices or “tuning” of exchange interactions. The relevance of this behavior in the study of NH4CuCl3 is discussed.